Violence against people over 65 years old – Lublin Voivodeship inhabitants - Rudnicka-Drożak, Ewa; Jankowski, Krzysztof; Jankowska, Paula; Majcher, Monika; Jankowska, Agnieszka (Journal of Education, Health and Sport, 2019)
Introduction In the majority of cases violence and aggression have been and are directed against women, and also the older ones. Nevertheless, the number of reported incidents of abuse and neglect of older people does not match the number of the cases discovered and treated. Objective The aim of the research was to determine the risk factors of violence against people over 65 years of age, with regard to all the forms of the phenomenon (psychological, physical, material and sexual violence and neglect). Material and methods This series of research were conducted from 1 September 2014 to 28 February 2015 in family doctor’s clinics in the Lublin Voivodeship chosen at random. The research participants comprised 1047 people. The methods applied included the analysis of both doctor’s and nurse’s medical documentation. Results The violence risk factors for the victim are as follows: old age, low level of education and dependency on other people. The worse situation of the people living in the country who are more frequently subject to almost all types of violence as compared with the city-dwellers. Violence against older people is a manifestation (very often ignored) of pathologies of family life. Conclusions Old age, low level of education and dependency on other people among elderly are the risk factors of becoming violence victim. There is worse situation of the people living in the country who are more frequently subject to almost all types of violence as compared with the city-dwellers. Violence against older people is a manifestation (very often ignored) of pathologies of family life.